2021
DOI: 10.14202/vetworld.2021.2444-2451
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among TonoVet, TonoVet Plus, Tono-Pen Avia Vet, and Kowa HA-2 portable tonometers for measuring intraocular pressure in dogs

Abstract: Background and Aim: Tonometers are an important instrument for measuring intraocular pressure (IOP) in the diagnosis of glaucoma or uveitis. This study aimed to compare the accuracy of the main types of tonometers with different IOP measurement methodologies in dogs: TonoVet and TonoVet Plus (rebound), Tono-Pen Avia Vet (applanation), and Kowa HA-2 (Goldmann applanation). Materials and Methods: IOP was measured in 152 eyes of 76 dogs. A postmortem study was performed by comparing manometry and tonometry value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…This is the first study to compare the accuracy of tonometers in horses using three different methodologies: rebound, applanation, and applanation by the Goldmann methodology, including the measurement of real IOP through in vivo manometry. Passareli et al 28 recently reported that Tonovet and Tonovet Plus were most suitable for daily clinical use in dogs as they are easy to handle and do not require the use of topical anaesthesia to measure IOP; however, all tonometers showed satisfactory accuracy for measuring IOP in dogs. In this study, Tonovet, Tonovet Plus, Tono‐Pen AVIA Vet, and Kowa HA‐2 also showed satisfactory accuracy in measuring IOP in horses, particularly Tonovet and Tonovet Plus, which proved to be easy to handle and did not require the use of topical anaesthetics, thus causing no discomfort to the animals.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to compare the accuracy of tonometers in horses using three different methodologies: rebound, applanation, and applanation by the Goldmann methodology, including the measurement of real IOP through in vivo manometry. Passareli et al 28 recently reported that Tonovet and Tonovet Plus were most suitable for daily clinical use in dogs as they are easy to handle and do not require the use of topical anaesthesia to measure IOP; however, all tonometers showed satisfactory accuracy for measuring IOP in dogs. In this study, Tonovet, Tonovet Plus, Tono‐Pen AVIA Vet, and Kowa HA‐2 also showed satisfactory accuracy in measuring IOP in horses, particularly Tonovet and Tonovet Plus, which proved to be easy to handle and did not require the use of topical anaesthetics, thus causing no discomfort to the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Direct and consensual PLRs were normal OU, but there was minimal pupillary dilation with DA OS. Intraocular pressure (Tonovet, Icare Finland, Vantaa, Finland) measured 19 mmHg OD and 21 mmHg OS (RI = 11.7–24.5 mmHg) 14 . There was no uptake of fluorescein dye OU and the palpebral reflex, corneal reflex, physiological nystagmus, menace response, dazzle reflex, visual following and visual placing were all unremarkable OU.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the TVP has a larger display screen and requires only one push of a button to acquire the 6 consecutive measurements needed to obtain each IOP value. A few studies validating use of the TVP in dogs 17,34 and rabbits, 23,35 have reported that IOPs obtained with the TVP correlate well with manometry in these species, particularly in the clinically relevant range of 5–50 mmHg 17,23 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the TVP has a larger display screen and requires only one push of a button to acquire the 6 consecutive measurements needed to obtain each IOP value. A few studies validating use of the TVP in dogs 17,34 and rabbits, 23,35 have reported that IOPs obtained with the TVP correlate well with manometry in these species, particularly in the clinically relevant range of 5-50 mmHg. 17,23 The objective of this study was to validate IOP measurements obtained with the TVP rebound tonometer in normal cats and cats with glaucoma and compare the accuracy and precision of the values to those obtained by the widely used TV01 and TP.…”
Section: Introductionmentioning
confidence: 99%